A phenomenological study investigating experiences of student learning using an online radiation therapy planning curriculum. (December 2022) - Osborne, Catherine; Merchant, Susan; Knight, Kellie; Sim, Jenny; Wright, Caroline
Highlights: Student engagement influences student experience with online education. The online environment afforded flexibility of learning, allowing students to remain in their hometown without the need to relocate to attend on campus study. The online radiation therapy planning curriculum provided opportunities for students to self-reflect, revisit learning resources and repeat the overall experiential learning cycle. The online radiation therapy planning curriculum, supported by clinical experts and academics created a safe space for the development of pre-clinical skills, assisting in transition to clinical placement. Students perceived an improved clinical readiness and confidence in interacting with clinical staff in clinical placement after engaging with the online radiation therapy planning curriculum. Abstract: Introduction: Traditionally radiation therapy planning was taught on campus in planning labs, or in the case of fully online programs, during clinical placements. In 2017, an innovative online planning curriculum was developed using a structured, self-directed approach of online learning and assessment, supported by a cloud-based planning system. This study aimed to explore student experiences of learning and practising planning online, and the application of acquired knowledge and skills to clinical practice. Methods: Student experiences were investigated using an interpretive phenomenological method. A purposive sample of under-graduate and graduate entry students was recruited through email and snowballing. A combination of online individual and group interviews were conducted. Two researchers analysed the data, and used reflection, discussion and note taking processes to immerse themselves in the data. Following data collection, the process of organising data for analysis, applying a coding and condensing process to reduce the data into themes and sub-themes was conducted. Results: Seventeen students from three cohorts participated in the interviews. Five key themes were identified: Flexibility, Connectedness, Personal relevance, Professional Experts and Safe environment. Sub-component themes were also identified. Discussion: Student engagement was based on a range of factors that influence the student experience. The planning curriculum allowed students to develop confidence and competence in pre-clinical planning skills prior to placement. Conclusion: Although initial experiences were overwhelming, over time students experienced a sense of engagement with their learning when supported by clinical and academic experts. Students felt more prepared for clinical placement as a result of their experiences.